Pemanfaatan Pengelolaan Kantin Sekolah untuk Pemahaman Konsep Ekonomi dan Keterampilan Berwirausaha Siswa SMAN 45 Maluku Tengah - Aminah Rehalat; Zuhria Nurul 'Ainy (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the utilization of school canteen management as a learning medium to enhance students’ understanding of economic concepts and entrepreneurial skills at SMAN 45 Central Maluku. The background of this research is based on the importance of contextual learning that integrates economic theory with real practice within the school environment. This research employed a qualitative approach with a descriptive study design. Data were collected through observation, interviews, and documentation involving the principal, canteen managers, economics teachers, and students. The findings reveal that school canteen management can function effectively as an entrepreneurship laboratory. Students not only understand basic economic concepts such as supply and demand, simple financial management, transaction recording, and profit-loss calculation, but also develop entrepreneurial skills including responsibility, creativity, communication, and decision-making. Furthermore, students’ direct involvement in canteen activities enhances discipline and teamwork. Therefore, school canteen management can serve as a practice-based learning facility that sustainably supports the improvement of students’ economic competencies and entrepreneurial spirit.